Laminate, circuit board, and method for manufacturing circuit board

The laminate structure with a specific surface roughness curve on the bonding surfaces of the metal layers enhances the adhesion reliability of metal-based circuit boards during high temperature treatments, addressing the issue of reduced adhesion and improving productivity.

JP7661114B2Active Publication Date: 2025-04-14DENKA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021079646
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-10
Publication Date
2025-04-14
Estimated Expiration
2041-05-10

AI Technical Summary

Technical Problem

Conventional metal-based circuit boards experience reduced adhesion reliability of the insulating layer after high temperature treatments, such as solder reflow, which can lead to solder cracks and compromised productivity.

Method used

A laminate structure comprising a first metal layer, an insulating layer, and a second metal layer, where at least one of the bonding surfaces exhibits a specific surface roughness curve with a reference length of 250 μm, an average length of RSm less than 100 μm, and a maximum height Rz of 1.0 μm or more, enhancing the adhesion reliability through high temperature treatments.

Benefits of technology

The proposed laminate structure effectively maintains high adhesion reliability of the metal-based circuit boards even after high temperature treatments, thereby improving productivity and reducing the occurrence of solder cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661114000004
    Figure 0007661114000004
  • Figure 0007661114000005
    Figure 0007661114000005
  • Figure 0007661114000001
    Figure 0007661114000001
Patent Text Reader

Abstract

To provide a laminate capable of forming a metal base circuit board capable of maintaining high bonding reliability even by high temperature treatment.SOLUTION: A laminate includes: a first metal layer; an insulation layer disposed on the first metal layer; and a second metal layer disposed on the insulation layer. At least one of a bonding face of the first metal layer with the insulation layer and a bonding face of the second metal layer with the insulation layer expresses a surface roughness curve having a standard length of 250 μm, an average length RSm of elements of 100 μm or shorter, and a maximum height Rz of 1.0 μm or higher.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate that is suitably used in the manufacture of a circuit board (metal-based circuit board), a circuit board, and a method for manufacturing a circuit board. [Background technology]

[0002] A variety of circuit boards have been put to practical use as circuit boards on which electronic and electrical components such as semiconductor elements are mounted to form hybrid integrated circuits. Circuit boards are classified based on the board material into resin circuit boards, ceramic circuit boards, metal-based circuit boards, etc.

[0003] Resin circuit boards are inexpensive, but because the thermal conductivity of the board is low, their applications are limited to those requiring relatively low power. Ceramic circuit boards, due to the characteristics of ceramics, such as high electrical insulation and heat resistance, are suitable for applications requiring relatively high power, but have the disadvantage of being expensive. On the other hand, metal-based circuit boards have intermediate properties between the two, and are suitable for general-purpose applications requiring relatively high power, such as inverters for refrigerators, inverters for commercial air conditioners, power sources for industrial robots, and power sources for automobiles.

[0004] For example, Patent Document 1 discloses a method for obtaining a circuit board having excellent stress relaxation properties, heat resistance, moisture resistance, and heat dissipation properties by using a composition for circuit boards containing a specific epoxy resin, a curing agent, and an inorganic filler as essential components. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-266533 A Summary of the Invention [Problem to be solved by the invention]

[0006] If ceramic circuit boards could be substituted for metal-based circuit boards, it would be possible to improve productivity. Ceramic circuit boards also have the problem that solder cracks are likely to occur on the board during heat cycles, but by substituting metal-based circuit boards, it is expected that the occurrence of solder cracks can be suppressed. Meanwhile, in the industrial module field where ceramic circuit boards are used, high-temperature treatments such as solder reflow treatments are performed, but with conventional metal-based circuit boards, the adhesive reliability of the insulating layer may decrease after high-temperature treatment.

[0007] Therefore, an object of the present invention is to provide a laminate capable of forming a metal base circuit board capable of maintaining high adhesive reliability even after high-temperature treatment. Another object of the present invention is to provide a metal base circuit board capable of maintaining high adhesive reliability even after high-temperature treatment, and a method for manufacturing the same. [Means for solving the problem]

[0008] One aspect of the present invention relates to a laminate comprising a first metal layer, an insulating layer disposed on the first metal layer, and a second metal layer disposed on the insulating layer, wherein at least one of a bonding surface of the first metal layer with the insulating layer and a bonding surface of the second metal layer with the insulating layer exhibits a surface roughness curve having a reference length of 250 μm, an average element length RSm of 100 μm or less, and a maximum height Rz of 1.0 μm or more.

[0009] In one embodiment, both a bonding surface of the first metal layer with the insulating layer and a bonding surface of the second metal layer with the insulating layer may exhibit the surface roughness curve.

[0010] In one embodiment, the insulating layer may have a thickness of 30 μm or more.

[0011] In one embodiment, the first metal layer and the second metal layer may contain 60 mass % or more of at least one metal atom selected from the group consisting of aluminum, copper, iron, silver, gold, zinc, nickel and tin.

[0012] In one embodiment, the insulating layer may contain a cured insulating resin and an inorganic filler.

[0013] Another aspect of the present invention relates to a circuit board comprising a metal layer, an insulating layer disposed on the metal layer, and a metal circuit portion disposed on the insulating layer, wherein at least one of a bonding surface of the metal layer with the insulating layer and a bonding surface of the metal circuit portion with the insulating layer exhibits a surface roughness curve having a reference length of 250 μm, an average element length RSm of 100 μm or less, and a maximum height Rz of 1.0 μm or more.

[0014] In one embodiment, both a joint surface of the metal layer with the insulating layer and a joint surface of the metal circuit portion with the insulating layer may exhibit the surface roughness curve.

[0015] Yet another aspect of the present invention relates to a method for manufacturing a circuit board, comprising the steps of preparing the above-mentioned laminate and removing a portion of the first metal layer or a portion of the second metal layer of the laminate to form a metal circuit portion. Effect of the Invention

[0016] According to the present invention, there is provided a laminate capable of forming a metal base circuit board capable of maintaining high adhesive reliability even after high-temperature treatment. Also, according to the present invention, there is provided a metal base circuit board capable of maintaining high adhesive reliability even after high-temperature treatment, and a method for manufacturing the same. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a laminate. [Diagram 2] FIG. 2 is a cross-sectional view illustrating an embodiment of a circuit board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Preferred embodiments of the present invention will now be described in detail.

[0019] [Laminate] The laminate of the present embodiment includes a first metal layer, an insulating layer disposed on the first metal layer, and a second metal layer disposed on the insulating layer. The laminate of the present embodiment can also be called a laminate for forming a circuit board.

[0020] In the laminate of this embodiment, at least one of the bonding surface (S1) of the first metal layer with the insulating layer and the bonding surface (S2) of the second metal layer with the insulating layer exhibits a surface roughness curve with a reference length of 250 μm, an average element length RSm of 100 μm or less, and a maximum height Rz of 1.0 μm or more.

[0021] According to the laminate of this embodiment, it is possible to form a metal base circuit board that can maintain high adhesion reliability even after high-temperature treatment. Although the reason why the laminate of this embodiment exhibits such an effect is not necessarily clear, it is thought that by roughening at least one of the metal layers to show the above-mentioned surface roughness curve, the interface between the metal layer and the insulating layer becomes more resistant to thermal stress during high-temperature treatment, and the deterioration of adhesion reliability due to high-temperature treatment is suppressed.

[0022] In this specification, the surface roughness curve is measured by a laser microscope (VK-X1000 manufactured by Keyence Corporation).

[0023] The mean element length (RSm) indicates the average length of the roughness curve elements in the reference length, and is a value calculated from the surface roughness curve in accordance with JIS B 0601. The maximum height (Rz) indicates the sum of the height of the highest peak (Rp) and the depth of the deepest valley (Rv) in the roughness curve in the reference length, and is a value calculated from the surface roughness curve in accordance with JIS B 0601.

[0024] In this embodiment, "exhibiting a specific surface roughness curve" means that a specific surface roughness curve is measured on at least a portion of the target surface.

[0025] (metal layer) The metal material constituting the first metal layer is not particularly limited and may be, for example, aluminum, copper, iron, silver, gold, zinc, nickel, tin, alloys containing these metals, etc. The first metal layer may be composed of one type of metal material, or may be composed of two or more types of metal materials.

[0026] The first metal layer preferably contains at least one metal atom (M1) selected from the group consisting of aluminum, copper, iron, silver, gold, zinc, nickel, and tin. The metal atom (M1) is preferably at least one selected from the group consisting of aluminum, copper, and iron, and more preferably at least one selected from the group consisting of aluminum and copper.

[0027] The content of the metal atom (M1) may be, for example, 50 mass% or more, preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on the total amount of the first metal layer, and may be 90 mass% or more, or may be 100 mass%.

[0028] The first metal layer may be, for example, a metal plate. The thickness of the first metal layer is not particularly limited, and may be, for example, 0.01 mm or more, preferably 0.1 mm or more, more preferably 1.0 mm or more. The thickness of the first metal layer may be, for example, 10 mm or less, preferably 5.0 mm or less, more preferably 3.0 mm or less.

[0029] The bonding surface (S1) of the first metal layer may be a surface that has been roughened. The method of roughening is not particularly limited, and any known roughening treatment can be used without particular limitation. Examples of the roughening treatment include chemical etching, blasting, and buffing.

[0030] The conditions for the roughening treatment are not particularly limited, and for example, conditions may be appropriately selected under which the joining surface (S1) exhibits a surface roughness curve (C) described below.

[0031] The metal material constituting the second metal layer is not particularly limited and may be, for example, aluminum, copper, iron, silver, gold, zinc, nickel, tin, alloys containing these metals, etc. The second metal layer may be composed of one type of metal material, or may be composed of two or more types of metal materials.

[0032] The second metal layer preferably contains at least one metal atom (M2) selected from the group consisting of aluminum, copper, iron, silver, gold, zinc, nickel, and tin. The metal atom (M2) is preferably at least one selected from the group consisting of aluminum, copper, and iron, and more preferably at least one selected from the group consisting of aluminum and copper.

[0033] The content of the metal atom (M2) may be, for example, 50 mass% or more, preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on the total amount of the second metal layer, and may be 90 mass% or more, or may be 100 mass%.

[0034] The second metal layer may be, for example, a metal foil. The thickness of the second metal layer is not particularly limited, and may be, for example, 0.01 mm or more, preferably 0.02 mm or more, more preferably 0.03 mm or more. The thickness of the second metal layer may be, for example, 5.0 mm or less, preferably 3.0 mm or less, more preferably 1.0 mm or less.

[0035] The bonding surface (S2) of the second metal layer may be a surface that has been roughened. The method of roughening is not particularly limited, and any known roughening treatment can be used without particular limitation. Examples of the roughening treatment include chemical etching, blasting, and buffing.

[0036] The conditions for the roughening treatment are not particularly limited, and for example, conditions may be appropriately selected under which the joining surface (S2) exhibits a surface roughness curve (C) described below.

[0037] It is preferable that the first metal layer and the second metal layer have a joint surface (S1 or S2) with the insulating layer that exhibits a surface roughness curve (C) with a reference length of 250 μm, an average element length (RSm) of 100 μm or less, and a maximum height (Rz) of 1.0 μm or more.

[0038] In the surface roughness curve (C), the average element length (RSm) is preferably 80 μm or less, more preferably 60 μm or less. Although there is no particular limitation on the lower limit of the average element length (RSm), from the viewpoint of suppressing the deterioration of electrical insulation caused by electric field concentration on the convex portions and obtaining a circuit board with superior insulation reliability, the average element length (RSm) is, for example, 0.1 μm or more, preferably 1.0 μm or more, more preferably 10 μm or more.

[0039] In the surface roughness curve (C), the maximum height (Rz) is preferably 1.5 μm or more, more preferably 2.0 μm or more. The upper limit of the maximum height (Rz) is not particularly limited, but from the viewpoint of suppressing the deterioration of electrical insulation caused by electric field concentration on the convex parts and obtaining a circuit board with superior insulation reliability, the maximum height (Rz) is, for example, 50 μm or less, preferably 35 μm or less, more preferably 20 μm or less.

[0040] (insulating layer) The insulating layer may be, for example, a layer containing a cured insulating resin and an inorganic filler.

[0041] The insulating resin cured body may be, for example, a cured body of a resin component containing a thermosetting resin and a curing agent.

[0042] Examples of thermosetting resins include epoxy resins, silicone resins, phenol resins, cyanate resins, melamine resins, urea resins, thermosetting polyimide resins, and unsaturated polyester resins. Of these, epoxy resins are preferred from the viewpoints of adhesion and electrical insulation.

[0043] The epoxy resin may be any resin that can be cured by a curing agent. Examples of the epoxy resin include bisphenol A type epoxy resin, bisphenol S type epoxy resin, bisphenol F type epoxy resin, hydrogenated bisphenol A type epoxy resin, polypropylene glycol type epoxy resin, polytetramethylene glycol type epoxy resin, naphthalene type epoxy resin, phenylmethane type epoxy resin, tetrakisphenolmethane type epoxy resin, biphenyl type epoxy resin, epoxy resin having a triazine ring, bisphenol A alkylene oxide adduct type epoxy resin, dicyclopentadiene type epoxy resin, cresol novolac type epoxy resin, phenol novolac type epoxy resin, etc. The epoxy resin may be used alone or in combination of two or more types.

[0044] The curing agent may be any curing agent capable of curing the thermosetting resin, and may be appropriately selected from known curing agents depending on the type of thermosetting resin.

[0045] When the thermosetting resin is an epoxy resin, examples of the curing agent (curing agent for epoxy resin) include amine-based curing agents, phenol-based curing agents, acid anhydride-based curing agents, and thiol-based curing agents.

[0046] The amine-based curing agent may be any curing agent that has an amino group and is capable of curing an epoxy resin. Examples of the amine-based curing agent include aromatic amine-based curing agents, aliphatic amine-based curing agents, and dicyandiamide.

[0047] As the amine-based curing agent, any amine-based curing agent known as a curing agent for epoxy resins can be used without any particular limitation. As the amine-based curing agent, a commercially available product may be used, and for example, an aliphatic polyamine, an alicyclic polyamine, an aromatic polyamine, etc. can be suitably used.

[0048] The phenol-based curing agent may be any curing agent that has a plurality of phenolic hydroxyl groups and is capable of curing an epoxy resin. Examples of the phenol-based curing agent include novolac-type phenolic resins and resol-type phenolic resins.

[0049] As the phenol-based curing agent, any phenol-based curing agent known as a curing agent for epoxy resins can be used without any particular limitation. As the phenol-based curing agent, a commercially available product may be used, and for example, phenol novolac, xylylene novolac, bisphenol A type novolac, etc. can be suitably used.

[0050] The acid anhydride curing agent may be any curing agent that has a structure in which two carboxyl groups are dehydrated and condensed and can cure an epoxy resin. Examples of the acid anhydride curing agent include aliphatic acid anhydrides and aromatic acid anhydrides.

[0051] As the acid anhydride-based curing agent, any acid anhydride-based curing agent known as a curing agent for epoxy resins can be used without any particular limitation. As the acid anhydride-based curing agent, a commercially available product may be used, and for example, a phthalic anhydride derivative, a maleic anhydride derivative, etc. can be suitably used.

[0052] The thiol-based curing agent may be any curing agent that has a plurality of mercapto groups and is capable of curing an epoxy resin. Examples of the thiol-based curing agent include an aliphatic thiol-based curing agent and an aromatic thiol-based curing agent.

[0053] As the thiol-based curing agent, any thiol-based curing agent known as a curing agent for epoxy resins can be used without any particular limitation. As the thiol-based curing agent, a commercially available product may be used, and for example, an aliphatic polythioether, an aliphatic polythioester, an aromatic-containing polythioether, etc. can be suitably used.

[0054] The content of the curing agent in the resin component may be, for example, 1.0 part by mass or more, preferably 10 parts by mass or more, more preferably 20 parts by mass or more, or may be 50 parts by mass or more, relative to 100 parts by mass of the thermosetting resin. The content of the curing agent may be, for example, 300 parts by mass or less, preferably 200 parts by mass or less, more preferably 150 parts by mass or less, or may be 0 parts by mass, relative to 100 parts by mass of the thermosetting resin.

[0055] The resin component may further contain other components than those described above. For example, the resin component may further contain a curing accelerator, a discoloration inhibitor, a surfactant, a coupling agent, a colorant, a viscosity modifier, an antioxidant, an ion scavenger, etc., as necessary.

[0056] The content of other components in the resin component may be, for example, 10% by mass or less, preferably 5% by mass or less, or even 0% by mass. That is, the total amount of the thermosetting resin and the curing agent in the resin component may be, for example, 90% by mass or more, preferably 95% by mass or more, or even 100% by mass.

[0057] The insulating resin cured body is a cured body of a resin component.

[0058] The glass transition point of the insulating resin cured body is preferably 125°C or higher, more preferably 150°C or higher. This improves the insulation resistance of the cured body at high temperatures, and an insulating layer with better insulation reliability at high temperatures can be formed. There is no particular upper limit to the glass transition point of the insulating resin cured body, but it is preferably 400°C or lower, more preferably 350°C or lower. This further improves the flexibility of the cured body, and an insulating layer with even better stress relaxation properties can be formed.

[0059] In this specification, the glass transition temperature of the insulating resin cured body refers to a value measured by the following method. <Method of measuring glass transition temperature> (1) Preparation of measurement samples The insulating resin cured body is cut into a plate of 0.1 mm x 5 mm x 40 mm size to prepare a measurement sample. (2) Measurement of glass transition temperature Using a dynamic viscoelasticity measuring device ("RSA 3" manufactured by T&A Instruments), the loss tangent (tan δ) is measured in the temperature range of 30°C to +300°C under conditions of a frequency of 10 Hz and a heating rate of 10°C / min. The temperature at which the loss tangent value is maximized is defined as the glass transition point.

[0060] The content of the cured insulating resin in the insulating layer may be, for example, 1.0% by volume or more, preferably 10% by volume or more, more preferably 20% by volume or more, based on the total volume of the insulating layer. The content of the cured insulating resin in the insulating layer may be, for example, 99% by volume or less, preferably 90% by volume or less, more preferably 80% by volume or less, based on the total volume of the insulating layer.

[0061] Examples of the inorganic filler include inorganic fillers composed of aluminum oxide, silica, aluminum nitride, silicon nitride, boron nitride, and the like.

[0062] From the viewpoint of suppressing the deterioration of electrical insulation in a high-temperature and high-humidity environment caused by hydrolysis of the inorganic material, the inorganic filler is preferably mainly composed of an inorganic material selected from the group consisting of aluminum oxide, silica, silicon nitride, and boron nitride. The content of the inorganic material in the inorganic filler is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, based on the total amount of the inorganic filler.

[0063] For example, when the inorganic filler contains a large amount of aluminum nitride, hydrolysis of the aluminum nitride may occur in a high-temperature and high-humidity environment, resulting in a decrease in electrical insulation. Therefore, the content of aluminum nitride in the inorganic filler is preferably 40 mass% or less, more preferably 30 mass% or less, and even more preferably 20 mass% or less, based on the total amount of the inorganic filler. As described above, by using an inorganic material selected from the group consisting of aluminum oxide, silica, silicon nitride, and boron nitride as the main component, the decrease in electrical insulation caused by such hydrolysis is significantly suppressed.

[0064] The shape of the inorganic filler is not particularly limited and may be particulate, scaly, polygonal, etc., with particulate being preferred.

[0065] The maximum particle size of the inorganic filler may be, for example, 250 μm or less, preferably 200 μm or less, more preferably 150 μm or less. This tends to further improve the electrical insulation of the insulating layer. The minimum particle size of the inorganic filler is not particularly limited, but from the viewpoint of further improving the thermal conductivity of the insulating layer, it may be, for example, 0.05 μm or more, preferably 0.1 μm or more. In this specification, the maximum particle size and the minimum particle size of the inorganic filler refer to the d90 diameter and the d10 diameter in the volume-based particle size distribution, which are measured by a laser diffraction type particle size distribution measuring device.

[0066] The content of the inorganic filler in the insulating layer may be, for example, 1.0% by volume or more, preferably 10% by volume or more, more preferably 20% by volume or more, based on the total volume of the insulating layer. The content of the inorganic filler in the insulating layer may be, for example, 99% by volume or less, preferably 90% by volume or less, more preferably 80% by volume or less, based on the total volume of the insulating layer.

[0067] The insulating layer can be formed, for example, by curing a coating of a composition containing the above-mentioned resin component and an inorganic filler.

[0068] The coating film can be cured, for example, by heat treatment. The heat treatment may be performed in one step or two steps. By performing the heat treatment in two steps, an insulating layer can be formed via a semi-cured coating film. The temperature and time of the heat treatment may be appropriately changed depending on the types of thermosetting resin and curing agent, etc.

[0069] When the heat treatment is carried out in one step, the heat treatment temperature may be, for example, 40 to 250° C., and preferably 70 to 180° C., and the heat treatment time may be, for example, 0.5 to 48 hours, and preferably 1 to 6 hours.

[0070] When the heat treatment is carried out in two stages, the temperature of the first stage heat treatment (first heat treatment) may be, for example, 40 to 150° C., and preferably 50 to 100° C., and the time of the first heat treatment may be, for example, 0.2 to 8 hours, and preferably 0.5 to 5 hours. The temperature of the second stage heat treatment (second heat treatment) may be, for example, 70 to 250° C., and preferably 120 to 180° C., and the time of the heat treatment may be, for example, 0.5 to 9 hours, and preferably 1 to 6 hours.

[0071] The insulating layer may be formed, for example, by placing a coating of the composition or a semi-cured product of the coating between a first metal layer and a second metal layer, and applying heat and pressure. The pressure conditions are not particularly limited. The pressure may be, for example, 1 MPa or more, preferably 5 MPa or more, more preferably 8 MPa or more. The pressure may be, for example, 30 MPa or less, preferably 25 MPa or less, more preferably 20 MPa or less.

[0072] The thickness of the insulating layer is not particularly limited, but from the viewpoint of electrical insulation, it may be, for example, 30 μm or more, preferably 50 μm or more, more preferably 80 μm or more, and from the viewpoint of thermal resistance, the thickness of the insulating layer may be, for example, 500 μm or less, preferably 300 μm or less, more preferably 200 μm or less.

[0073] Fig. 1 is a cross-sectional view showing a preferred embodiment of a laminate. The laminate 10 shown in Fig. 1 includes a first metal layer 1, an insulating layer 2 disposed on the first metal layer 1, and a second metal layer 3 disposed on the insulating layer 2. The first metal layer 1 has a bonding surface S1 with the insulating layer 2. The second metal layer 3 has a bonding surface S2 with the insulating layer 2.

[0074] At least one of the joining surface S1 and the joining surface S2 exhibits the above-mentioned surface roughness curve (C).

[0075] The second metal layer 3 of the laminate 10 is processed into a predetermined shape to form a metal circuit portion, whereby a circuit board can be easily manufactured.

[0076] It is preferable that the portion of the bonding surface S1 of the first metal layer 1 facing the metal circuit portion exhibits the above-mentioned surface roughness curve. It is also preferable that the portion of the bonding surface S2 of the second metal layer 3 remaining as the metal circuit portion exhibits the above-mentioned surface roughness curve (C). In other words, it is preferable that the metal circuit portion is formed at a position facing the portion of the bonding surface S1 that exhibits the above-mentioned surface roughness curve (C). It is also preferable that the metal circuit portion is formed so that the portion of the bonding surface S2 that exhibits the above-mentioned surface roughness curve (C) remains.

[0077] There are no particular limitations on the method for forming the metal circuit portion, and any known processing method may be used.

[0078] [Circuit board] The circuit board of the present embodiment includes a metal layer, an insulating layer disposed on the metal layer, and a metal circuit portion disposed on the insulating layer.

[0079] In the circuit board of this embodiment, at least one of the bonding surface (S1) of the metal layer with the insulating layer and the bonding surface (S3) of the metal circuit portion with the insulating layer exhibits a surface roughness curve (C) having a reference length of 250 μm, an average element length RSm of 100 μm or less, and a maximum height Rz of 1.0 μm or more.

[0080] The circuit board of this embodiment can maintain high adhesive reliability even after high-temperature treatment. Although the reason why the circuit board of this embodiment exhibits such an effect is not necessarily clear, it is believed that by roughening at least one of the metal layer and the metal circuit portion to show the above-mentioned surface roughness curve (C), the interface between the metal layer or the metal circuit portion and the insulating layer can more easily withstand the thermal stress during high-temperature treatment, and thus the deterioration of adhesive reliability due to high-temperature treatment is suppressed.

[0081] The circuit board of the present embodiment may be manufactured by removing a portion of the second metal layer of the above-mentioned laminate.

[0082] In the circuit board of this embodiment, the surface roughness curve (C) may be similar to the surface roughness curve (C) in the laminate described above.

[0083] The metal layer in the circuit board of this embodiment may be, for example, the same as the first metal layer in the laminate described above.

[0084] The insulating layer in the circuit board of this embodiment may be the same as the insulating layer in the laminate described above.

[0085] The metal circuit portion in the circuit board of the present embodiment may be a remainder obtained by removing a part of the second metal layer in the laminate described above. That is, the material constituting the metal circuit portion and the thickness of the metal circuit portion may be the same as the material constituting the second metal layer and the thickness of the second metal layer.

[0086] Fig. 2 is a cross-sectional view showing a preferred embodiment of a circuit board. The circuit board 20 shown in Fig. 2 is a circuit board manufactured from the laminate shown in Fig. 1, and includes a first metal layer 1, an insulating layer 2 disposed on the first metal layer 1, and a metal circuit portion 4 disposed on the insulating layer 2. The first metal layer 1 has a bonding surface S1 with the insulating layer 2. The metal circuit portion 4 has a bonding surface S3 with the insulating layer 2.

[0087] At least one of the joining surface S1 and the joining surface S3 exhibits the above-mentioned surface roughness curve (C).

[0088] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments.

[0089] The present invention may relate to a method for producing a laminate, comprising, for example, a first preparation step of preparing a first metal layer having a roughened surface in which the average element length RSm in a surface roughness curve having a reference length of 250 μm is 100 μm or less and the maximum height Rz is 1.0 μm or more; a second preparation step of preparing a second metal layer having a roughened surface in which the average element length RSm in a surface roughness curve having a reference length of 250 μm is 100 μm or less and the maximum height Rz is 1.0 μm or more; a third preparation step of preparing a composition containing a resin component containing a thermosetting resin and a curing agent and an inorganic filler; an arrangement step of arranging a coating film of the composition or a semi-cured body thereof between the first metal layer and the second metal layer arranged so that the roughened surfaces face each other; and a heating and pressing step of forming an insulating layer by heating and pressing to obtain a laminate including the first metal layer, the insulating layer, and the second metal layer.

[0090] The first preparation step may be a step of roughening one surface of a metal layer to form a first metal layer, or a step of measuring a surface roughness curve of a metal layer having a roughened surface, the roughened surface having a reference length of 250 μm, and selecting a first metal layer based on an average length RSm and a maximum height Rz of elements in the surface roughness curve.

[0091] The second preparation step may be a step of roughening one surface of the metal layer to form a second metal layer, or a step of measuring a surface roughness curve of a metal layer having a roughened surface, the roughened surface having a reference length of 250 μm, and selecting a second metal layer based on an average length RSm and a maximum height Rz of elements in the surface roughness curve.

[0092] The present invention may also relate to a sorting method for sorting a laminate comprising a first metal layer, an insulating layer disposed on the first metal layer, and a second metal layer disposed on the insulating layer.

[0093] The above-mentioned selection method may include a first selection step of measuring a surface roughness curve having a reference length of 250 μm for the joint surface (S1) of the first metal layer with the insulating layer, and selecting laminates having an average element length RSm of 100 μm or less and a maximum height Rz of 1.0 μm or more in the surface roughness curve.

[0094] The above selection method may also include a second selection step of measuring a surface roughness curve having a reference length of 250 μm for the joint surface (S2) of the second metal layer with the insulating layer, and selecting laminates having an average element length RSm of 100 μm or less and a maximum height Rz of 1.0 μm or more in the surface roughness curve.

[0095] The above-mentioned selection method may include one of a first selection step and a second selection step, or may include both.

[0096] The present invention may further relate to a sorting method for sorting a circuit board including a metal layer, an insulating layer disposed on the metal layer, and a metal circuit portion disposed on the insulating layer.

[0097] The above-mentioned selection method may include a first selection step of measuring a surface roughness curve having a reference length of 250 μm for the joint surface (S1) of the metal layer with the insulating layer, and selecting circuit boards having an average element length RSm of 100 μm or less and a maximum height Rz of 1.0 μm or more in the surface roughness curve.

[0098] The above selection method may also include a second selection step of measuring a surface roughness curve having a reference length of 250 μm for the joint surface (S3) of the metal circuit portion with the insulating layer, and selecting circuit boards having an element average length RSm of 100 μm or less and a maximum height Rz of 1.0 μm or more in the surface roughness curve.

[0099] The above-mentioned selection method may include one of a first selection step and a second selection step, or may include both. EXAMPLES

[0100] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0101] Example 1 <Preparation of Composition> As a thermosetting resin, naphthalene-type epoxy resin HP-4032D (manufactured by DIC Corporation, specific gravity 1.2 g / cm 3 ) 100 parts by mass, and phenol novolac resin VH-4150 (DIC Corporation, specific gravity 1.1 g / cm) as a hardener. 3 ) and 12.4 parts by mass of boron nitride (manufactured by Denka Co., Ltd., specific gravity 2.27 g / cm 3 ) 214.8 parts by mass, and a wetting and dispersing agent DISPER BYK111 (manufactured by BYK-Chemie, specific gravity 1.1 g / cm 3 ) 0.7 parts by mass, and TPP (manufactured by Hokko Chemical Industry Co., Ltd., specific gravity 1.1 g / cm 3 ) 0.6 parts by mass, and an imidazole compound 2PHZ-PW (manufactured by Shikoku Chemical Industry Co., Ltd., specific gravity 1.1 g / cm 3 ) and 1.0 part by mass were mixed and stirred for 15 minutes in a planetary mixer to prepare a composition. The content by volume of each component in the composition was 43.6% by volume of naphthalene type epoxy resin, 5.9% by volume of phenol novolac resin, 49.4% by volume of boron nitride, 0.3% by volume of wetting dispersant, 0.3% by volume of hardening accelerator, and 0.5% by volume of imidazole compound.

[0102] <Preparation of Laminate> The obtained composition was applied onto a polyethylene terephthalate (PET) film having a thickness of 0.038 mm so that the thickness after semi-curing was 0.20 mm, and the film was dried by heating at 100°C for 70 minutes to produce a semi-cured body (B-stage sheet). The obtained semi-cured body was peeled off from the PET film and placed on the roughened surface of a metal plate (copper plate having a thickness of 2.0 mm). Next, the roughened surface of a metal foil (copper foil having a thickness of 0.5 mm) was placed on the semi-cured body, and then the film was heated and cured at 180°C for 410 minutes while applying a surface pressure of 10 MPa with a press machine to obtain a laminate. The thickness of the insulating layer in the laminate was 125 μm.

[0103] The roughened surfaces of the metal plate and metal foil were measured for surface roughness curves by the method described below, and the average length RSm and maximum height Rz of the elements were determined. The results are shown in Table 1. The glass transition temperature of the cured resin constituting the insulating layer was also measured. The results are shown in Table 1.

[0104] <Creating a circuit board> After masking predetermined positions on the metal foil of the laminate with an etching resist, the copper foil was etched using a sulfuric acid-hydrogen peroxide mixed solution as an etching solution. The etching resist was removed, and the substrate was washed and dried to obtain a metal base circuit board having a circular electrode (copper foil) with a diameter of 20 mm. The adhesion reliability of the obtained metal base circuit board was evaluated by the following method. The results are shown in Table 1.

[0105] <Surface roughness curve measurement> The roughened surfaces of the metal plate and metal foil were observed using a laser microscope VK-X1000 (Keyence Corporation), and a surface roughness curve with a reference length of 250 μm was obtained using line roughness measurement with data analysis software, and RSm and Rz were calculated using the method specified in JIS B 0601. The measurement conditions were an objective lens of x50 and an eyepiece of x approximately 20, and data was obtained from one location.

[0106] <Evaluation of Adhesion Reliability> First, as a destructive test, the circuit board was heated on a hot plate at 285°C for 5 minutes, then cooled to room temperature, and the metal plate and metal foil were peeled off from the insulating layer. In this destructive test, adhesion reliability was evaluated as follows: A if cohesive failure occurred in the insulating layer, and B if interfacial failure occurred at the interface between the metal plate and the insulating layer, or at the interface between the metal foil and the insulating layer.

[0107] (Examples 2 to 10 and Comparative Examples 1 to 2) A laminate and a circuit board were produced in the same manner as in Example 1, except that the metal plate and metal foil used had the average element length RSm and maximum height Rz on the roughened surface shown in Table 1, Table 2, or Table 3. The adhesion reliability of the obtained circuit board was evaluated in the same manner as in Example 1. The results are shown in Table 1, Table 2, or Table 3.

[0108] Example 11 <Preparation of Composition> As a thermosetting resin, bisphenol A type epoxy resin EXA-850CRP (DIC Corporation, specific gravity 1.2 g / cm 3 ) 100 parts by mass, and diaminophenylmethane H-84B (D Acmex Corporation, specific gravity 1.1 g / cm) as a hardener. 3 ) 34 parts by mass, and alumina AS30-1 (manufactured by Showa Denko K.K., specific gravity 3.95 g / cm 3 The composition was prepared by stirring and mixing 900 parts by mass of the bisphenol A epoxy resin, 9.0% by volume of the curing agent, and 66.6% by volume of the alumina AS30-1 in the composition for 15 minutes using a planetary mixer.

[0109] <Preparation of Laminate> The obtained composition was applied onto a polyethylene terephthalate (PET) film having a thickness of 0.038 mm so that the thickness after semi-curing was 0.20 mm, and the film was dried by heating at 100°C for 20 minutes to produce a semi-cured body (B-stage sheet). The obtained semi-cured body was peeled off from the PET film and placed on the roughened surface of a metal plate (aluminum plate having a thickness of 1.5 mm). Next, the roughened surface of a metal foil (copper foil having a thickness of 0.5 mm) was placed on the semi-cured body, and the film was heated and cured at 180°C for 410 minutes while applying a surface pressure of 10 MPa with a press machine to obtain a laminate. The thickness of the insulating layer in the laminate was 130 μm.

[0110] The surface roughness curves of the roughened surfaces of the metal plate and metal foil were measured in the same manner as in Example 1, and the average length RSm and maximum height Rz of the elements were determined. The results are shown in Table 2. The glass transition temperature of the cured resin constituting the insulating layer was also measured. The results are shown in Table 2.

[0111] <Creating a circuit board> After masking predetermined positions on the metal foil of the laminate with an etching resist, the copper foil was etched using a sulfuric acid-hydrogen peroxide mixed solution as an etching solution. The etching resist was removed, and the substrate was washed and dried to obtain a metal base circuit board having a circular electrode (copper foil) with a diameter of 20 mm. The adhesion reliability of the obtained metal base circuit board was evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0112] [Table 1]

[0113] [Table 2]

[0114] [Table 3] [Explanation of symbols]

[0115] 1...first metal layer, 2...insulating layer, 3...second metal layer, 4...metal circuit portion, 10...laminated body, 20...circuit board.

Claims

1. a first metal layer; an insulating layer disposed on the first metal layer; a second metal layer disposed on the insulating layer; Equipped with At least one of a joint surface of the first metal layer with the insulating layer and a joint surface of the second metal layer with the insulating layer exhibits a surface roughness curve having a reference length of 250 μm, an average element length RSm of 10 μm or more and 60 μm or less, and a maximum height Rz of 2.0 μm or more and 35 μm or less, the insulating layer contains a cured insulating resin and an inorganic filler, The insulating resin cured body is a cured body of a resin component containing an epoxy resin and a curing agent.

2. The laminate according to claim 1 , wherein both a joint surface of the first metal layer with the insulating layer and a joint surface of the second metal layer with the insulating layer exhibit the surface roughness curve.

3. The laminate according to claim 1 or 2, wherein the insulating layer has a thickness of 30 μm or more.

4. The laminate according to any one of claims 1 to 3, wherein the first metal layer and the second metal layer contain 60 mass% or more of at least one metal atom selected from the group consisting of aluminum, copper, iron, silver, gold, zinc, nickel, and tin.

5. A metal layer, an insulating layer disposed on the metal layer, and a metal circuit portion disposed on the insulating layer, At least one of a joint surface of the metal layer with the insulating layer and a joint surface of the metal circuit portion with the insulating layer exhibits a surface roughness curve having a reference length of 250 μm, an average element length RSm of 10 μm or more and 60 μm or less, and a maximum height Rz of 2.0 μm or more and 35 μm or less, the insulating layer contains a cured insulating resin and an inorganic filler, The circuit board, wherein the insulating resin cured body is a cured body of a resin component containing an epoxy resin and a curing agent.

6. The circuit board according to claim 5 , wherein both a joint surface of the metal layer with the insulating layer and a joint surface of the metal circuit portion with the insulating layer exhibit the surface roughness curve.

7. A step of preparing a laminate according to any one of claims 1 to 4; removing a portion of the first metal layer or a portion of the second metal layer of the laminate to form a metal circuit portion; A method for manufacturing a circuit board, comprising:

Citation Information

Patent Citations

  • Metal base laminated board

    JP1985127783A

  • Metal base laminated board

    JP1985149189A

  • Metal based substrate and manufacture thereof

    JP1987037995A

  • Method for constructing coke oven and temporary shed for constructing the coke oven

    JP2008266533A

  • Epoxy resin composition, epoxy resin sheet, and metal base circuit board using the same

    JP2016155953A